THE EFFECTIVENESS OF GOAT MILK TO INCREASE THE VOLUME OF BREAST MILK AND PROTEIN CONTENT AMONG LACTATING WOMEN: RANDOMIZED CONTROLLED TRIAL EVIDENCE - Reviana, Prita Alvina; Dewi, Yulia Lanti Retno; Widyaningsih, Vitri (Indonesian Journal of Medicine, 2019)
Background: Breast milk is a natural food to fulfill the nutritional needs of infants during the first 6 months of life. Nutrition is one of the factors that influence milk production. Protein is one of the most important nutrient factors needed by nursing mothers to increase milk production. This study aimed to analyze the effectiveness of giving goat milk to increase breast milk production.Subject and Method: A randomized controlled trial (RCT) was conducted in Madiun, East Java, in October 2019. A sample of 100 lactating mothers who had infants aged 1-3 months was selected by purposive sampling and divided into 2 groups. The dependent variables were an increase in milk production and protein intake. The independent variable was the effectiveness of giving goat milk. The data were collected by observation and 24-hour food recall sheets. The data were analyzed by t test run on Stata 13 program.Results: After having goat milk, the average of breast milk production in the intervention group (Mean= 121.5; SD= 12.81) was higher than in the control group (Mean= 97.06; SD= 13.59), (ES= 0.81; p<0.001). Protein intake after having goat milk was higher in the intervention group (Mean= 92.60; SD= 4.54) than control group (Mean 83.36; SD= 4.26), (ES= 2.10; p < 0.001).Conclusion: Goat milk is effective for increasing milk production and protein intake in lactating mothers.Keywords: goat milk, breast milk, proteinCorrespondence: Prita Alvina Reviana, Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta, Central Java, Indonesia. Email: pritasessy@gmail.com. Mobile: +6282334673976Indonesian Journal of Medicine (2019), 4(4): 364-370https://doi.org/10.26911/theijmed.2019.04.04.09